Pembuatan dan Pengujian Mekanik hasil Sambungan Las Pipa ASS 316L Menggunakan Proses GTAW - Riswanda, Riswanda; Wahyudin, Faris Khoiri; Sugianto, Sugianto; Mulyana, Deni; Saragih, Albert Daniel (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Gas tungsten arc welding (GTAW) is a welding process that is widely used for stainless steel materials, especially material thicknesses below 3 mm. In this study, ASS 316L pipes with a diameter of 89 mm, a thickness of 2.6 mm, and a length of 100 mm using a current of 50A was successful prepared. The type of welding wire used is ER316L with a diameter of 1.6 mm and argon as a shielding gas with using a backing gas. The results of macrograph observations showed that the face tended to be concave and the root experienced over penetration. This was correlated with the results of visual observations, including the face in the weld metal area being lower than the base metal and the root being too deep. The highest average tensile test result is 659 MPa, with a yield strength of 484 MPa, while the elongation is 39.3%, then the fracture form occurs minimal necking or brittle fracture occurs. The highest average hardness test result in the WM area is 188 HV, followed by the HAZ area with an average hardness of 154 HV and in the WM area an average hardness of 148 HV.